2007
DOI: 10.1890/06-1060.1
|View full text |Cite
|
Sign up to set email alerts
|

What Matters for Predicting the Occurrences of Trees: Techniques, Data, or Species' Characteristics?

Abstract: Abstract. Data characteristics and species traits are expected to influence the accuracy with which species' distributions can be modeled and predicted. We compare 10 modeling techniques in terms of predictive power and sensitivity to location error, change in map resolution, and sample size, and assess whether some species traits can explain variation in model performance. We focused on 30 native tree species in Switzerland and used presenceonly data to model current distribution, which we evaluated against i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
258
3
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(281 citation statements)
references
References 49 publications
15
258
3
5
Order By: Relevance
“…The advantage of ME is that it can be fitted with a low number of presence-only observations and that it is able to model possibly non-linearly relationships. Another advantage of ME compared to RF, which was also reported by Guisan et al [78], was that the accuracy was not affected applying cross-validation. This indicated that RF was more prone to overfitting than ME.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The advantage of ME is that it can be fitted with a low number of presence-only observations and that it is able to model possibly non-linearly relationships. Another advantage of ME compared to RF, which was also reported by Guisan et al [78], was that the accuracy was not affected applying cross-validation. This indicated that RF was more prone to overfitting than ME.…”
Section: Discussionmentioning
confidence: 56%
“…The accuracy of GLM and RF are negatively influenced by small sample sizes (e.g., [23,78,79]). The advantage of ME is that it can be fitted with a low number of presence-only observations and that it is able to model possibly non-linearly relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the indicator species analysis provides no information on drought susceptibility. These species (and also P. sylvestris [planted]) as elements of early-successional forest phases generally are considered as difficult to model with respect to their climate dependence (Guisan et al 2007) and are ranked low in terms of favorability (see table 3) with the exception of P. avium.…”
Section: Comparison Of the Different Drought Tolerance Rankingsmentioning
confidence: 99%
“…via its interaction with the use of pseudo-absences. Th ere are several approaches for generating pseudo-absence points (Pearce and Boyce 2006), including selecting points randomly (McPherson et al 2004), randomly with caseweighting to reduce the eff ective sample size of pseudo-absences (Guisan et al 2007), or via environmentally weighted random sampling (Zaniewski et al 2002). Th is selection of approach can aff ect the outcomes of the models (Engler et al 2004), but the pros and cons of diff erent approaches remain open to debate (Chefaoui and Lobo 2008).…”
Section: Mainmentioning
confidence: 99%
“…Many recent studies have adopted a strategy of selecting a set of pseudo-absences from the overall set of assumed absence data points to be used in the model calibration (e.g. McPherson et al 2004, Guisan et al 2007. Th e pseudo-absence approach may be a particularly attractive option when the modelling is based on atlases, museum data and databases.…”
Section: Introductionmentioning
confidence: 99%